Detoxification of comfrey (Symphytum officinale L.) extract using natural deep eutectic solvent (NADES) and evaluation of its anti-inflammatory, antioxidant, and hepatoprotective properties - Andiri Niza Syarifah; Andiri Niza Syarifah; Herman Suryadi; Hayun Hayun; Adelina Simamora; Adelina Simamora; Abdul Mun'im; Abdul Mun'im (Frontiers Media S.A., 2023)
Comfrey (Symphytum officinale L.) contains rosmarinic acid which has different pharmacological activities, such as antioxidant and anti-inflammatory activities. However, the medicinal use of comfrey is limited by the hepatotoxic effect of lycopsamine in comfrey, which overshadows the health benefits of rosmarinic acid. Natural deep eutectic solvents (NADES) have a wide range of extraction properties, that provides a new approach to the detoxification of comfrey. In the present study, betaine-based and choline chloride-based NADES were screened for selective extraction of rosmarinic acid over lycopsamine. Ultrasonication was used in conjunction with NADES extraction. The chemical profile of the NADES extracts on antioxidant, anti-inflammatory and hepatotoxic activities were investigated using some chemical reagents. Betaine-urea (1:2 molar ratio, 50% water) obtained the highest content of rosmarinic acid and a low level of lycopsamine (1.934 and 0.018 mg/g, respectively). Betaine-urea was also shown to be more effective to extract rosmarinic acid compared to methanol-UAE under the same conditions, which gave lower rosmarinic acid and higher lycopsamine levels (0.007 and 0.031 mg/g, respectively). Betaine-urea extracts showed higher antioxidant and anti-inflammatory properties as compared with other NADES extracts, however, had lower hepatotoxic profile. This study recommends the use of betaine-urea to detroxify comfrey to open wider opportunities for the development of comfrey for medicinal use.